WEBSITE APPLICATIONS SHIPPING USING MACROMEDIA DREAMWEAVER MX - Nasrul Nasrul; Yudi Irawan Chandra, SKom., MMSI Yudi Irawan Chandra, SKom., MMSI (Jurnal Sistem Informasi, 2007)
Website navigation application program is created using Macromedia DreamweaverMX program whose goal is to create a web application program that displays on thevoyage into an Internet network that can be opened by anyone who is interested andalso want to learn or understand from about shipping. From the home.htm page wecan move to the next page with a link without having to return to the home page.Use Frame, Link and others in making this program a facility has been provided byMacromedia Dreamweaver MX to facilitate the creation in making a web page.